(untitled) (Stavební obzor - Civil Engineering Journal, 2021)
This experiment’s objective is to prove that the reinforcing rib’s form contributes to its bond strength. The specimen is the concrete cubes measuring 150 × 150 × 150 mm; bar installed in the center of the concrete cube. Bars use 13, 16, and 19 mm diameters. For comparison, the experiment was also carried out on plain reinforcement diameter with 12 mm, 16 mm, and 19 mm. Concrete compression is fc’ 34 MPa. The pullout test was also performed to increase the load in stages at a 200 kg/minute speed. Loading stopped if the reinforcement yielded, split concrete, or slipped bar. The experiment uses ASTM standards ASTM C234-91a. The study results are the bond strength on reinforcement with the surrounding concrete. Bond strength in the plain bar is lower than deformed. The reinforcement of steep rib compared to fishbone bond strength values incline to be the same. The ratio of the bond strength of plain compared to deformed is 15% - 18%. The bond index of the steep rib and fishbone rib between 0.11 - 0.16 so that the bond stress obtained is also relatively the same. The failure pattern that occurs is determined based on the bond stress-slip graph. There are two types of collapse in this experiment, namely pullout and splitting damage. The failure of each specimen based on the diameter and shape of the rib varies greatly. The splitting damage is seen visually only in the specimen of the D19 fishbone rib.